Leisured intimacy in organizational settings: An exploratory investigation - Theocharous, Antonis L.; Philaretou, Andreas G. (My University, 2011)
This investigation focuses on the dynamics of sexuality and leisure intimate relationships in organizational settings. It aims primarily at: (a) mapping out the micro social psychological variants of sexuality and intimate relationships in formal bureaucratic structures, such as those between a graduate student and a professor in an academic setting, and (b) delineating the meso- and macrosociological reasons for the social construction of such a phenomenon. Data was collected and analyzed using autoethnographic research methodologies, in particular, obtrusive and unobtrusive participant observation field study techniques. Results indicate that, in general, sexuality is socially constructed and privately experienced in organizational settings, and, therefore cannot be eradicated but only controlled. It is up to the organization to develop, establish, and maintain an appropriate organizational culture, encompassing an array of both formal as well as informal policies, that will aim at effectively and efficiently guiding and regulating its members' intrapersonal emotional and psychological feeling states as well as interpersonal behaviors towards achieving desirable organizational ends with minimal interpersonal disruption. Common Ground, Valentine J. Belfiglio, All Rights Reserved.
Keywords: Sexuality; Intimacy; Social Construction; Organization; Bureaucracy